Respuestas fisiológicas de materiales de soja en simbiosis con micorrizas bajo estrés por sequía - Menduni, M.F.; Salloum, M.S.; Luna, Celina Mercedes; Monteoliva, Mariela Ines; Guzzo, María Carla (REDBIO, 2021)
Poster